Phylogenetic relationship among Libellula, Ladona and Plathemis (Odonata: Libellulidae) based on DNA sequence of mitochondrial 16S rRNA gene - Kambhampati, Srinivas; Charlton, Ralph E. (Systematic entomology, 1999)
. The type genus for the dragonfly family Libellulidae is Libellula. At present, Libellula s.l. includes twenty‐nine species, whose distribution is largely Nearctic. Whether two other libellulid taxa, Ladona and Plathemis, should be considered synonyms of Libellula, subgenera of Libellula, or separate genera, has been a subject of intermittent debate for over a century. Earlier proposals concerning Ladona and Plathemis were based on a limited number of morphological characters and lacked rigorous phylogenetic analyses. Therefore, we used the DNA sequence of a portion of the mitochondrial 16S rRNA gene and parsimony, maximum likelihood and neighbour‐joining analyses to explore whether Ladona and Plathemis are monophyletic lineages distinct from Libellula. We obtained ≈ 415 bp of DNA sequence from twenty‐three taxa including thirteen species of Libellula s.s., all three recognized species of Ladona, the two species of Plathemis and representatives of four other libellulid genera. Tetragoneuria williamsoni (Odonata: Corduliidae) was included as the outgroup. Parsimony analysis suggested that Ladona and Plathemis are monophyletic lineages distinct from Libellula s.s. with a sister group relationship between Libellula and Ladona. The monophyly of Ladona, Plathemis and Libellula was supported in > 90% of bootstrap replications and in trees five to ten steps longer than the most parsimonious trees. Relationships inferred from maximum likelihood and neighbour‐joining analyses also supported the monophyly of Ladona and Plathemis. The four other libellulid genera included in the study formed a monophyletic clade distinct from Libellula, Ladona and Plathemis. Based on our analysis, we propose that Ladona and Plathemis be considered either genera or subgenera within Libellulidae.